Diseño, implementación del plan de comunicación en la Organización Kallari productores de cacao y chocolate - Macas Palacios, Estefanía Mishel (2013)
This field work with social links had its origins in the necessity to design a plan of communication for an Agency integrated by a group of Kichwa people that works in the fields producing cocoa and chocolate in the city of Tena, Napo province,. The name of the organization is Asociación Agro Artesanal de Producción de Bienes Agrícolas Pecuarios y Piscícolas del Napo, Kallari and it was created under the initiative of GTZ, a German entity that specializes in international technical cooperation for development of sustainable programs as part of the Ministry of Agriculture, Livestock and Fisheries (Ministerio de Agricultura, Ganadería, Acuacultura y Pesca - MAGAP). This entity works closely with the Association in the execution of this and other projects.